Increasing Hurricane Intensification Rate Near the US Atlantic Coast. Issue 20 (17th October 2022) - Balaguru, Karthik; Foltz, Gregory R.; Leung, L. Ruby; Xu, Wenwei; Kim, Dongmin; Lopez, Hosmay; West, Robert
Abstract: Hurricanes often cause severe damage and loss of life, and storms that intensify close to the coast pose a particularly serious threat. While changes in hurricane intensification and environment have been examined at basin scales previously, near‐coastal changes have not been adequately explored. In this study, we address this using a suite of observations and climate model simulations. Over the 40‐year period of 1979–2018, the mean 24‐hr hurricane intensification rate increased by ∼1.2 kt 6‐hr −1 near the US Atlantic coast. However, a significant increase in intensification did not occur near the Gulf coast over the same period. The enhanced hurricane intensification along the Atlantic coast is consistent with an increasingly favorable dynamic and thermodynamic environment there, which is well simulated by climate models over the historical period. Further, multi‐model projections suggest a continued enhancement of the storm environment and hurricane intensification near the Atlantic coast in the future. Plain Language Summary: While hurricanes pose a significant socioeconomic threat in general, those that intensify close to the coast are particularly challenging for operational forecasters and decision makers. Past studies examined basin‐scale changes in hurricane intensification and the large‐scale environment in the Atlantic. However, near‐coastal changes in hurricane intensification have not been extensively studied. Herein, we address this using a combination of observations and numerical model simulations. Analysis of hurricane track data for the period 1979–2018 indicates that the mean hurricane intensification rate has increased significantly near the Atlantic coast. In contrast, significant increases in nearshore hurricane intensification are not seen for the Gulf coast. Observed changes in the ambient storm environment over the same period, which are in good agreement with these changes in hurricane intensification, are well reproduced by climate models. Finally, models project a continued enhancement of the hurricane environment near the Atlantic coast in the future. These results are well supported by direct simulation of hurricanes in high‐resolution climate models. Key Points: Hurricane intensification rate has significantly increased near the US Atlantic coast over the last 40 years Climate models accurately simulate the observed trends with an enhanced environment conducive for hurricanes Multi‐model projections suggest that the environment will increasingly favor hurricane intensification near the Atlantic coast